ANALISIS PERBANDINGAN RISK&RETURN PORTOFOLIO SAHAM FIRST LINER& SECOND LINER DENGAN METODE INDEKS TUNGGAL (Studi Kasus Pada Saham-Saham Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2012-2014) - astawinetu, erwin dyah; soebrati, ni wayan (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRACTInvestors generally will invest their fund in stocks that have high return with minimal risk in the capital market. In order to reduce level of risk then the stocks should be formed into portfolio. The purpose of this research is to analyze the risks & return of stocks of the first & the second liner of food & beverages companies that are listed in Indonesia stock exchange (IDX) from 2012 to 2014. A single index model is used for research method. The data observed based on historical data of the closing stock-price of food & beverages companies listed. Technique of taking sample uses purposive sampling. The sample used in this research is 12 (twelve) stocks of the food & beverages companies from 2012 to 2014 which are listed in Indonesia stock exchange (IDX).Data analysis using T-test (independent sample t-test) with significance level of 5%. The first hypothesis using Independent t-test shows that there is no significant return between first liner and second liner stocks. The second hypothesis using Independent t-test shows that there is no significant risk between the two as well.This research shows that investing in the second liner stocks are more profitable than investing in the first liner stocks because the return of the second liner stocks are higher than the first liners’ while the risks of the second liner stocks are lower than the first liners’.  Keywords : Single Index Model, First Liner Stock, Second Liner Stock